Functioning and satisfaction with health services of persons living with spinal cord injuries in the Western Cape during the COVID-19 pandemic - Du Plessis, Herne (Stellenbosch : Stellenbosch University, 2024)
Thesis (MScPhysio)--Stellenbosch University, 2024.